Penguatan Keterampilan Komunikasi dan Kepercayaan Diri Melalui Public Speaking: Penerapan Metode Presentasi dan Bermain Peran di Kalangan Siswa SMP - Sukmasetya, Pristi; Dwihantoro, Prihatin (Civiliza Publishing, 2024)
Public speaking is an essential skill that should be mastered by all individuals, including middle school students, as it is valuable not only in academic settings but also in social and professional contexts. This community service initiative aims to enhance public speaking skills and boost the confidence of middle school students through a combination of presentation and role-playing methods. The training consisted of a series of sessions where students were given opportunities to prepare and deliver structured presentations, as well as practice speaking in simulated, real-life scenarios. The results of the program showed significant improvement in both the verbal and non-verbal communication skills of the students. Those who initially lacked confidence became more capable of organizing effective presentations, utilizing appropriate body language, and responding to their audience effectively. Additionally, the training helped students overcome anxiety associated with public speaking, increasing their courage to speak in front of others. While some students may still require a more personalized approach, the overall methods proved to be effective in developing public speaking skills. This training is expected to provide long-term benefits in students' soft skill development and could serve as a sustainable program within schools.